PENGISLAHAN SISTEM PENDIDIKAN ISLAM DI TANAH MELAYU: PERANAN MUDIR MADRASAH AL-MASHOOR AL-ISLAMIAH PULAU PINANG, 1916-1957 (Reformation of Islamic Education System in Malaya: The Role of Mudir Madrasah al-Mashoor al-Islamiah Penang, 1916-1957) - Muhamad, Ahmad Dzulfahmi; Othman, Mohammad Redzuan (Journal of Al-Tamaddun, 2020)
This study discusses the reformation of the Islamic education system in Malaya, especially in Penang before independence, from 1916 to 1957. The period is considered to be one of the most important periods in the Islamic education system in Malaya in the formal development of Islamic Education institutions in Malaya and the role played by the mudir madrasah in the modernization of the Islamic education system. The methodology of this study uses qualitative methods and library studies to analyze the primary and secondary sources. The findings of this study show that the Mudir Madrasah al-Mashoor al-Islamiah initiated by Syed Sheikh al-Hadi and later, Sheikh Abdullah al-Maghribi and Sheikh Abbas Bakar Rafiee have played an important role in the efforts to reform the Islamic education system. The reformation of the Islamic Education system in Madrasah al-Mashoor al-Islamiah can be examined by improving aspects of administration, curriculum and co-curriculum, founding of a madrasah for women and setting up its branches in Sabak Bernam Selangor and Balik Pulau Penang.